\(8x^2-2x=0\Rightarrow4x\left(x-2\right)=0.\)
\(\Rightarrow\orbr{\begin{cases}x=0\\\left(x-2\right)=0\end{cases}\Rightarrow x\in\left\{0;2\right\}}\)
\(8x^2-2x=0\)
\(\Leftrightarrow x\left(8x-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\8x-2=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\frac{1}{4}\end{cases}}\)
\(8x^2-2x=0\)
\(\Leftrightarrow2x\left(4x-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}2x=0\\4x-1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\frac{1}{4}\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=\frac{1}{4}\end{cases}}\)
\(8\times^2-2\times=0\)
\(\Rightarrow2\times\left(4\times-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}\times=0\\4\times-1=0\end{cases}\Rightarrow}\orbr{\begin{cases}\times=0\\\times=\frac{1}{4}\end{cases}}\)
8x2 - 2x = 0
<=> 2x(4x - 1) = 0
<=> \(\orbr{\begin{cases}2x=0\\4x-1=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=0\\x=\frac{1}{4}\end{cases}}\)
Vậy ...
\(8x^2-2x=0\)
\(\Leftrightarrow2x\left(4x-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}2x=0\\4x-1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=0\\4x=1\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=0\\x=\frac{1}{4}\end{cases}}}\)
Vậy\(x=0;\frac{1}{4}\)
\(8x^2-2x=0\)
\(2x\left(4x-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}2x=0\\4x-1=0\end{cases}}\) \(\Rightarrow\text{ }\orbr{\begin{cases}x=0\\4x=0+1=1\end{cases}}\) \(\Rightarrow\orbr{\begin{cases}x=0\\x=\frac{1}{4}\end{cases}}\)
\(\Rightarrow\text{ }x\in\left\{0\text{ ; }\frac{1}{4}\right\}\)
Bài làm
8x2 - 2x = 0
=> 2x( 4x - 1 ) = 0
=> 2x = 0 => x = 0
hoặc ( 4x - 1 ) = 0 => x = 1/4
Vậy x = 0 hoặc x = 1/4
# Học tốt #